Characterization of circulating microRNA profiles of postpartum dairy cows with persistent subclinical endometritis - Gonçalo Pereira; Gilles Charpigny; Yongzhi Guo; Elisabete Silva; Marta Filipa Silva; Tao Ye; Luís Lopes-da-Costa; Patrice Humblot (Journal of Dairy Science, 2023)
ABSTRACT: Subclinical endometritis (SCE) is an unresolved inflammation of the endometrium of postpartum dairy cows, seriously affecting fertility. Current diagnosis, which relies on uterine cytology or even more invasive biopsy sampling, would benefit from the identification of blood-based diagnostic biomarkers. Due to the known role of microRNAs (miRNAs) in other diseases, this case-control study evaluated the cell-free circulating miRNA profiles of SCE cows, and the network of transcripts predicted to interact with those miRNAs, previously identified as differentially expressed genes (DEG) in the endometrium of the same cows. Healthy (H, n = 6) and persistent SCE (n = 11) cows characterized by endometrial cytology and biopsy were blood sampled at 21 and 44 d postpartum (DPP). Following extraction of cell-free plasma miRNAs and RNA-seq analysis, differential abundance analysis of miRNAs was performed with the DESeq2 R package (adjusted p-value of 0.05), and in silico prediction of miRNA-interacting genes on a sequence complementary basis was conducted using the miRWalk database. The principal component analysis showed a clear clustering between groups of uterine health phenotypes (H vs. SCE), although the clustering between groups was less pronounced at 44 DPP than at 21 DPP. No effect of the stage (21 vs. 44 DPP) was observed. A total of 799 known circulating miRNAs were identified, from which 34 demonstrated differential abundance between H and SCE cows (12 less abundant and 22 more abundant in SCE than in H cows). These 34 miRNAs are predicted to interact with 10,104 transcripts, among which 43, 81, and 147 were previously identified as differentially expressed in, respectively, endometrial luminal epithelial, glandular epithelial, and stromal cells of the same cows. This accounts for approximately half of the DEG identified between those H and SCE cows, including genes involved in endometrial cell proliferation, angiogenesis and immune response, whose dysregulation in SCE cows may impair pregnancy establishment. From 219 miRNAs with mean normalized read counts above 100, the presence and abundance of miR-425–3p and miR-2285z had the highest discriminatory level to differentiate SCE from H cows. In conclusion, despite apparent confinement to the endometrium, SCE is associated with a distinct circulating miRNA profile, which may represent a link between the systemic changes associated with disease and the endometrial immune response. The validation of a miRNA panel consisting of circulating cell-free miR-425–3p and miR-2285z may prove a relevant advancement for the noninvasive diagnosis of persistent SCE.